2004
DOI: 10.1177/000313480407000303
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Appendectomy in Children: Technically Feasible and Safe in All Stages of Acute Appendicitis

Abstract: This is a retrospective outcomes analysis of pediatric open and laparoscopic appendectomy in a children's hospital. One hundred three children underwent appendectomy for appendicitis by two pediatric surgeons from August 1998 to December 2002. Patients were divided into two groups, laparoscopic appendectomy (LAP) and open appendectomy (OAP), and were further subdivided by diagnosis: normal (NL), acute (AA), and ruptured (RA). There were no differences in age, sex, race, or zip codes between groups. Median age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 13 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…However, there is controversy regarding the application of laparoscopy for complicated appendicitis. [5][6][7][8][9][10][11][12][13][14] Our experience suggests that even under a trainee's hands, laparoscopy is quite safe for all stages of acute appendicitis. We lay more importance on thorough peritoneal lavage and bowel walking from the ileocecal junction proximally to release inter-loop adhesions and drain the pus cavities.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, there is controversy regarding the application of laparoscopy for complicated appendicitis. [5][6][7][8][9][10][11][12][13][14] Our experience suggests that even under a trainee's hands, laparoscopy is quite safe for all stages of acute appendicitis. We lay more importance on thorough peritoneal lavage and bowel walking from the ileocecal junction proximally to release inter-loop adhesions and drain the pus cavities.…”
Section: Discussionmentioning
confidence: 78%
“…Despite individual reports favouring open appendectomies, various meta-analysis give LA a reluctant edge, concluding that it is either better than or at least as effective as open appendectomy. [5][6][7][8][9][10][11][12][13][14] We aimed to examine, from a trainee's point of view, the application of laparoscopic approach for suspected appendicitis in children through a retrospective analysis of results of LA performed by a trainee laparoscopic surgeon, with an emphasis on laparoscopic training and the safety and efficacy of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting finding in our laparoscopy series was the extremely low conversion rate (1.6%), demonstrating that laparoscopy in expert hands is a safe and effective procedure. 13,33 In conclusion, laparoscopy seems to offer advantages and certainly no disadvantages compared with open surgery in cases of paediatric appendicitis. This retrospective study, comparing LA versus OA in children, failed to identify any major difference between the 2 techniques in terms of operating time or complication rate; indeed, it appears that the laparoscopic and the open techniques are similar in most respects and are equally safe modalities.…”
Section: Discussionmentioning
confidence: 93%
“…However, this average combines perforated and nonperforated cases. Studies that have distinguished between perforated and nonperforated appendicitis have reported higher costs for LA [25, 26].…”
Section: Discussionmentioning
confidence: 99%